Application of High-Throughput Sequencing on the Chinese Herbal Medicine for the Data-Mining of the Bioactive Compounds - Liu, Xiaoyan; Gong, Xun; Liu, Yi; Liu, Junlin; Zhang, Hantao; Qiao, Sen; Li, Gang; Tang, Min (Frontiers in Plant Science, 2022)
The Chinese Herbal Medicine (CHM) has been used worldwide in clinics to treat the vast majority of human diseases, and the healing effect is remarkable. However, the functional components and the corresponding pharmacological mechanism of the herbs are unclear. As one of the main means, the high-throughput sequencing technologies (HTS) have been employed to discover and parse the active ingredients of CHM. Moreover, a tremendous amount of effort is made to uncover the pharmacodynamic genes associated with the synthesis of active substances. Here, based on the genome-assembly and the downstream bioinformatics analysis, we present a comprehensive summary of the application of HTS on CHM for the synthesis pathways of active ingredients from two aspects: active ingredient properties and disease classification, which are important for pharmacological, herb molecular breeding, and synthetic biology studies.